Highly effective lead (II) removal by sustainable alkaline activated β-lactoglobulin nanofibrils from whey protein. (10th May 2020) - Zhang, Qingrui; Zhang, Shuaiqi; Zhao, Zhixue; Liu, Meng; Yin, Xiaofeng; Zhou, Yanping; Wu, Yun; Peng, Qiuming
Abstract: In this work, we developed β-lactoglobulin nanofibrils by alkaline-thermal activation methods for Pb removal. The protein fibrils exhibited effective adsorption and selectivity for lead (II) removal, even with coexisting Ca 2+ /Mg 2+ /Na + ions at higher concentrations. Kinetic results proved rapid Pb purification within 60 s. The nanofibrils effectively treated ∼22 m 3 contaminated water/kg sorbent, far beyond effectiveness of a commercial ion exchange resin. The effluent from this process approached to the drinking water standard recommended by the World Health Organization (10 μg/L). These satisfactory performances can be ascribed to the ultrafine nanofibril structures and abundance of amino-acid species of protein. The simple fabrication and efficient performance of these nanofibrils make them highly capable of alleviating Pb contamination problems. Graphical abstract: Image 1 Highlights: We developed β-lactoglobulin nanofibrils from Whey protein. It exhibited a rapid Pb removal in 60 s. It revealed favorable adsorption and superior selectivity. Outstanding treated capacity of 22 m 3 water/kg sorbent with regenerated property.